Information technology competency to invigorate innovative performance in Malaysian academic libraries / Haziah Sa'ari - Sa'ari, Haziah (Faculty of Information Management, 2015)
By playing a pivotal role in birth of entrepreneurial venture and advanced economic development, information technology (IT) has become a pervasive and major contributor in all sectors. In order to support the business functions and sustain competitiveness, management should assure their employees are embodied with the IT competency to innovatively perform in meeting business objectives at high level capacity. IT competency is defined as the capability of organization or an individual to manipulate and exploit the IT technologies, in order to manage information effectively. Innovative performance can be described as the capability to generate and exploit ideas with intention to create and performing new objectives, or present old ideas in new dynamic ways when executing work and/or managing business venture. The objective of this study is to investigate the influence of IT competency and explore derivative outcomes which are perceived as innovative performance as demonstrated by academic librarians in Malaysian research universities. Thusly, by using qualitative method and the employment of multiple case studies to achieve the desired objectives, this study is significant to academic librarians and library management for improving the IT competency and upgrading their innovation performance. It will also assist the Ministry of Higher Education, in addition to interested researchers to provide effective base line information in constructing a model for similar studies.